Cyclopiazonic Acid-Induced Ca2+ Store Depletion Initiates Endothelium-Dependent Hyperpolarization-Mediated Vasorelaxation of Mesenteric Arteries in Healthy and Colitis Mice - Zhang, Lu Yun; Chen, Xiong Ying; Dong, Hui; Xu, Feng (Frontiers in Physiology, 2021)
Purposes: Since the role of store-operated calcium entry (SOCE) in endothelium-dependent hyperpolarization (EDH)-mediated vasorelaxation of mesenteric arteries in health and colitis is not fully understood, cyclopiazonic acid (CPA), a specific inhibitor of the sarco(endo) plasmic reticulum calcium-ATPases (SERCA), was used as a SOCE activator to investigate its role in normal mice and its alteration in colitis mice. Methods: The changes in Ca2+ signalling in vascular endothelial cells were examined by single cell Ca2+ imaging and tension of mesenteric arteries in response to CPA were examined using Danish DMT520A microvascular measuring system. Results: CPA activated the SOCE through depletion of the ER Ca2+ in endothelial cells. CPA had a concentration-dependent vasorelaxing effect in endothelium-intact mesenteric arteries, which was lost after endothelial removal. Both NO and PGI2 inhibitors did not affect CPA-induced vasorelaxation; however, after both NO and PGI2 were inhibited, KCa channel blocker (10 mM TEA) inhibited CPA-induced vasorelaxation while KCa channel activator (0.3 µM SKA-31) promoted it. Two SOCE blockers (30 µM SKF96365 and 100 µM flufenamic acid), and an Orai channel blocker (30 µM GSK-7975A) inhibited this vasorelaxation. The inhibition of both Na+/K+-ATPase (NKA) and Na+/Ca2+-exchange (NCX) also inhibited CPA-induced vasorelaxation. Finally, the CPA involved in EDH-induced vasorelaxation by the depletion of ER Ca2+ of mesenteric arteries was impaired in colitis mice. Conclusions: Depletion of ER Ca2+ by CPA induces a vasorelaxation of mesenteric arteries that is mediated through endothelium-dependent hyperpolarization (EDH) mechanism and invokes the activation of SOCE. The CPA-induced endothelium-dependent dilation is impaired in colitis which may limit blood perfusion to the intestinal mucosa.